Mean maximal power from an on-water 1000-m time-trial predicts lactate threshold power in well-trained flat-water sprint kayak athletes - Hogan, C.; Binnie, M. J.; Doyle, M.; Peeling, P. (European Journal of Sport Science, 2022)
This study utilised on-water graded exercise tests (GXT) to determine the power output (PO) corresponding to the first and second lactate thresholds (LT1PO and LT2PO), subsequently examining their relationship to the mean maximal power (MMP) and race time achieved across three on-water sprint kayak time-trials. Twelve well-trained sprint kayak athletes completed an on-water GXT and a 200-, 500- and 1000-m time-trial utilising novel instrumented paddle technology. Stepwise multiple regression was used to determine whether equations incorporating 200-, 500- and 1000-m MMP data could be used as an alternative method for estimating LT1PO and LT2PO. On-water GXT derived LT1PO and LT2PO were 151 ± 34 and 194 ± 39 W, respectively. For the 200-, 500- and 1000-m time-trials, MMP were 528 ± 143, 358 ± 92 and 287 ± 67 W, respectively. Athletes` LT1PO and LT2PO had very-large inverse relationships to 200-, 500- and 1000-m time-to-completion (r = -.71 to -.85, P = .010) and very-large, to near-perfect positive relationships to 200-, 500- and 1000-m MMP (r = .81 to .94, P = .001). The equation incorporating 1000-m MMP alone provided the best prediction of LT1PO and LT2PO, explaining 78% and 88% of the variance, and yielding a standard error of estimate (SEE) of 11.3% and 7.1% for these measures, respectively. The results of this study provide further evidence to support the ecological validity of recently developed on-water GXTs graded by PO, since LT1PO and LT2PO were significantly correlated to 200-, 500- and 1000-m performance. Practitioners could also predict LT2PO with reasonable accuracy based solely from a 1000-m time-trial; potentially providing an alternative, non-invasive, competition-specific protocol for threshold determination.